Examining the Behavioral Biases Influencing on ESG Investing: A Systematic Review using PRISMA - Amgain, Pushpa Nidhi (Journal of Interdisciplinary Studies, 2024)
The aims of this study are to review past research on the relationship between behavioral biases and decision making in environmental, social, and governance (ESG) investing. Data were collected from three databases (Google Scholar, JSTOR and Research 4 Life) using PRISMA in the context of behavioral biases and environmental, social, and governance (ESG) investing time frame from 2013 to 2023. The 2013 was the base period due to the cause of the Governance pillar in the Eurozone for ESG investing. The inclusion criteria for this review were publication published in the English language, open access articles, and only peer-reviewed articles. The findings of the study show that there is a significant relationship between behavioral biases and ESG investing. The researcher found that there are more male participants in the capital market and 35 distinct biases examining the ESG decision by investors with non-probability techniques to collect samples. This study extends the existing knowledge on the past study being research related to a relationship between behavioral biases and ESG investing. This study assists researchers, academicians, and policymakers in understanding the behavioral biases of investors while making ESG investing decisions. Further research can be carried out by researchers in other contexts pension funds, and life insurance as there are no studies undertaken in these areas.